Beyond Artificial Intelligence The Disappearing Human-Machine Divide - Romportl, Jan.; Zackova, Eva.; Kelemen, Jozef; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is an edited collection of chapters based on the papers presented at the conference “Beyond AI: Artificial Dreams” held in Pilsen in November 2012. The aim of the conference was to question deep-rooted ideas of artificial intelligence and cast critical reflection on methods standing at its foundations.  Artificial Dreams epitomize our controversial quest for non-biological intelligence, and therefore the contributors of this book tried to fully exploit such a controversy in their respective chapters, which resulted in an interdisciplinary dialogue between experts from engineering, natural sciences and humanities.   While pursuing the Artificial Dreams, it has become clear that it is still more and more difficult to draw a clear divide between human and machine. And therefore this book tries to portrait such an image of what lies beyond artificial intelligence: we can see the disappearing human-machine divide, a very important phenomenon of nowadays technological society, the phenomenon which is often uncritically praised, or hypocritically condemned. And so this phenomenon found its place in the subtitle of the whole volume as well as in the title of the chapter of Kevin Warwick, one of the keynote speakers at “Beyond AI: Artificial Dreams”.    .
The Disappearing Human-Machine Divide -- How We're Predicting AI - or Failing to -- Intelligence Explosion Quest for Humankind -- Cyborg Tales: The Reinvention of the Human in the Information Age -- Heteronomous Humans and Autonomous Agents: Toward Artifcial Relational Intelligence -- Moral Enhancement and Artifcial Intelligence: Moral AI? -- Emotion, Artifcial Intelligence, and Ethics -- The Stuff that Dreams Are Made of: AI in Contemporary Science Fiction -- Why Are We Afraid of Robots? The Role of Projection in the Popular Conception of  Robots -- A Visit on the Uncanny Hill -- Desire-Based Model of Reasoning -- A Computational Behavior Model for Life-Like Intelligent Agents -- From Gobble to Zen -- Answering Curious Questions about Artifcial Intelligence -- Biological and Artifcial Machines -- Naturalness of Artifcial Intelligence.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence